Levels the Materiality of Taste and Artificial Intelligence - Abdala Moreira , Karina Astrid (E|C, 2023)
This article presents the main issues to be taken into account when analyzing the taste experience and its relationship with artificial intelligence. For this purpose, I base on a qualitative methodology. Firstly, I understand that to analyze this phenomenon there are different levels of taste and for each “level” there is a “translation” in terms of Lotman (1993). To distinguish the levels, I base on Hjelmslev’s linguistic analysis, understanding what happens at the level of expression and the level of content when we pass from the form to the substance and the matter of the taste experience. As far as artificial intelligence is concerned, I focus on the philosophical issues in this area. To conclude I present how the media discourse of this new mode of taste experience is presented by using the classic storytelling that appears in the gastronomy field.